Question and Answers Forum

All Questions      Topic List

Limits Questions

Previous in All Question      Next in All Question      

Previous in Limits      Next in Limits      

Question Number 94764 by Hamida last updated on 20/May/20

Answered by prakash jain last updated on 20/May/20

1a (i)  lim_(x→3) =1 (top point of semicircle)  1a(ii)  lim_(x→−1^− ) =0   1a(iii)  lim_(x→0^+ ) =0  (iv)  function is not continous at f(0)  lim_(x→0^− ) f(x)=0=lim_(x→0^+ ) f(x)  However f(0) =2  (v)   lim_(x→3^− ) f(3)=1=lim_(x→3^+ ) f(x)  To makd function continuous  f(3) value should be changed to 1.

1a(i)limx3=1(toppointofsemicircle)1a(ii)limx1=01a(iii)limx0+=0(iv)functionisnotcontinousatf(0)limx0f(x)=0=limx0+f(x)Howeverf(0)=2(v)limx3f(3)=1=limx3+f(x)Tomakdfunctioncontinuousf(3)valueshouldbechangedto1.

Commented by prakash jain last updated on 20/May/20

lim_(x→0) (((√(2x^2 +4))−6)/(x^2 −2x−8))  lim_(x→0) (((√(2x^2 +4))−6)/(x^2 −2x−8))×(((√(2x^2 +4))+6)/((√(2x^2 +4))+6))  lim_(x→0) ((2x^2 +4−36)/((x−4)(x+2)))×(1/((√(2x^2 +4))+6))  lim_(x→0) ((2x^2 −32)/((x−4)(x+2)))×(1/((√(2x^2 +4))+6))  lim_(x→0) ((2(x+4)(x−4))/((x−4)(x+2)))×(1/((√(2x^2 +4))+6))  lim_(x→0) ((2(x+4))/((x+2)))×(1/((√(2x^2 +4))+6))  put x=4  =((2×8)/6)×(1/(12))=(2/9)

limx02x2+46x22x8limx02x2+46x22x8×2x2+4+62x2+4+6limx02x2+436(x4)(x+2)×12x2+4+6limx02x232(x4)(x+2)×12x2+4+6limx02(x+4)(x4)(x4)(x+2)×12x2+4+6limx02(x+4)(x+2)×12x2+4+6putx=4=2×86×112=29

Commented by student work last updated on 21/May/20

   ans: (1/2)

ans:12

Answered by mathmax by abdo last updated on 21/May/20

let f(x) =(((√(2x^2 +4))−6)/(x^2 −2x−8))  we have x^2 −2x−8 =x^2 −16 −2x+8  =(x−4)(x+4)−2(x−4) =(x−4)(x+4−2) =(x−4)(x+2)  lim_(x→4) f(x) =lim_(x→4)     (((2x^2 +4−36)/((√(2x^2 +4))+6))/((x−4)(x+2)))  =lim_(x→4)     ((2x^2 −32)/((x−4)(x+2)((√(2x^2 +4))+6)))  =lim_(x→4)    ((2(x−4)(x+4))/((x−4)(x+2)((√(2x^2 +4))+6)))   =lim_(x→4)    ((2x+8)/((x+2)((√(2x^2 +4))+6))) =((16)/(4(12))) =((4×4)/(4×3×4)) =(1/3)

letf(x)=2x2+46x22x8wehavex22x8=x2162x+8=(x4)(x+4)2(x4)=(x4)(x+42)=(x4)(x+2)limx4f(x)=limx42x2+4362x2+4+6(x4)(x+2)=limx42x232(x4)(x+2)(2x2+4+6)=limx42(x4)(x+4)(x4)(x+2)(2x2+4+6)=limx42x+8(x+2)(2x2+4+6)=164(12)=4×44×3×4=13

Commented by prakash jain last updated on 21/May/20

=lim_(x→4)    ((2x+8)/((x+2)((√(2x^2 +4))+6))) =((16)/(4(12))) =((4×4)/(4×3×4)) =(1/3)  Calculation mistake shown in red  x+2=6  so it should be=((16)/(6×12))=(2/9)

=limx42x+8(x+2)(2x2+4+6)=164(12)=4×44×3×4=13Calculationmistakeshowninredx+2=6soitshouldbe=166×12=29

Terms of Service

Privacy Policy

Contact: info@tinkutara.com